Immuno-modulatory role of baicalin in atherosclerosis prevention and treatment: current scenario and future directions - Wang, Li; Huang, Shenyi; Liang, Xiaolun; Zhou, Junliang; Han, Yifan; He, Jiangshan; Xu, Danping (Frontiers in Immunology, 2024)
Atherosclerosis (AS) is recognized as a chronic inflammatory condition characterized by the accumulation of lipids and inflammatory cells within the damaged walls of arterial vessels. It is a significant independent risk factor for ischemic cardiovascular disease, ischemic stroke, and peripheral arterial disease. Despite the availability of current treatments such as statins, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, and lifestyle modifications for prevention, AS remains a leading cause of morbidity and economic burden worldwide. Thus, there is a pressing need for the development of new supplementary and alternative therapies or medications. Huangqin (Scutellaria baicalensis Georgi. [SBG]), a traditional Chinese medicine, exerts a significant immunomodulatory effect in AS prevention and treatment, with baicalin being identified as one of the primary active ingredients of traditional Chinese medicine.Baicalin offers a broad spectrum of pharmacological activities, including the regulation of immune balance, antioxidant and anti-inflammatory effects, and improvement of lipid metabolism dysregulation. Consequently, it exerts beneficial effects in both AS onset and progression. This review provides an overview of the immunomodulatory properties and mechanisms by which baicalin aids in AS prevention and treatment, highlighting its potential as a clinical translational therapy.